Clinical Ethics Informatics: An Initial Survey. - Frye III, John W. (Journal of Hospital Ethics)
Context: Ethics consultation in the US is widely used and reported in the literature, but multi-site comparison studies and data sharing across institutions are largely unknown or at least unreported. Objective: To better understand the different methods used by ethics services to record, taxonomize, analyze, and utilize data regarding their case consultations. Design: a 37-item questionnaire surveying persons who are "familiar with their ethics consultation database". Participants: A convenience sample of ethics service personnel recruited from several e-mail lists known to have ethics consultants among their subscribers. Results: A total of 53 unique surveys were completed. There was wide variety in institution's bed-size, consult volume, and ethics staffing among respondents. Recording practices for cases were similarly varied, with some institutions merely keeping paper documents with no analysis, others used spreadsheets with rudimentary analysis, and high-volume services employing specific programs or electronic medical record functions to provide a more robust analysis of various case features. The data recorded followed ASBH guidelines to varying degrees. Respondents reported a general desire for some standardization of recording methods and data types/inputs, which would be necessary before significant data sharing across institutions can be feasible or valuable.